Soil Acidity and its Management Options in Ethiopia: A Review (International Journal of Scientific Research and Management (IJSRM), 2019)
Soil acidity is one of the chemical soil degradation problems which affect soil productivity in the Ethiopian highlands. This paper tries to put together soil acidity concept, causes, extent and management practices. Soil acidity is the problem of agricultural activities in Ethiopian highlands (cultivated lands) and is getting an increase. Farmers require simple and sustainable techniques to amend acid soils and improve yields of crops of their choices. Recommendations on reclamation of acid soils need to change with new developments, such as liming, use of acid-tolerant crop varieties, integrated soil fertility management, and using of organic fertilizers. Liming has played an important role in raising soil pH and enhancing crop productivity. In Ethiopia, the gap between potential and actual yield is very wide because of soil acidity and associated nutrient availability. Acidic soils are not responsive to the application of inorganic fertilizers without amendments-it is simply wastage of resources. Thus, developing effective and efficient acid soil management practices is indispensable for enhancing crop productivity and thereby sustaining yield gains. This review focuses on the causes and managements of soil acidity and its subsequent effect on soil fertility and crop yield. It also provides important information on management options to amend soil acidity and improve the entire fertility of soils, and other organic amendments that can be applied to remedy soil acidity to the desired pH level and improve soil quality. Integrated acid soil management enhances the stability of yields and maximizes nutrient use efficiency.